2015
DOI: 10.1128/jcm.00714-15
|View full text |Cite
|
Sign up to set email alerts
|

Changes in MMP-9 and TIMP-1 Concentrations in Cerebrospinal Fluid after 1 Week of Treatment of Childhood Bacterial Meningitis

Abstract: We explored the changes of the initially highly upgraded cerebrospinal fluid matrix metalloproteinase 9 (MMP-9) and tissue inhibitor of MMP 1 (TIMP-1) response during recovery of childhood bacterial meningitis and their association with outcome. The sizes of these changes varied substantially, but a steeper decrease in the MMP-9 and an increase of the TIMP-1 concentrations augured a better outcome. Matrix metalloproteinases (MMPs) are a group of zinc-dependent enzymes which, through their ability to degrade ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
3
12
1
Order By: Relevance
“…MMP-9 inhibition by specific blocking antibodies partially abrogated BBB disruption. Our data is consistent with studies in multiple sclerosis, Alzheimer’s disease and bacterial meningitis where MMP-9 drove BBB dysfunction and neuronal injury 22 , 25 , 33 , 34 . VEGF expression has also been implicated in BBB disruption 35 , and a study in paediatric TB meningitis reported that VEGF levels correlated with CSF-serum albumin ratios and mononuclear cell counts 36 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…MMP-9 inhibition by specific blocking antibodies partially abrogated BBB disruption. Our data is consistent with studies in multiple sclerosis, Alzheimer’s disease and bacterial meningitis where MMP-9 drove BBB dysfunction and neuronal injury 22 , 25 , 33 , 34 . VEGF expression has also been implicated in BBB disruption 35 , and a study in paediatric TB meningitis reported that VEGF levels correlated with CSF-serum albumin ratios and mononuclear cell counts 36 .…”
Section: Discussionsupporting
confidence: 92%
“…Increased MMP-9 was also detected in brain biopsies of patients with CNS TB 19 , and elevated MMP-9 concentrations in the CSF were associated with tissue injury and death 20 . Similarly, expression of the collagenase MMP-1 and stromelysin MMP-3 were increased in brain biopsies of patients with CNS TB 21 and were independent predictors of death 22 . To target MMP dysregulation, host directed therapy with MMP inhibitors has been investigated in CNS inflammatory conditions such as multiple sclerosis 23 .…”
Section: Introductionmentioning
confidence: 95%
“…is reduced compared to the acute phase of infection [144]. In pediatric PM, MMP-9 levels were found to correlate with CSF cell counts, with high CSF MMP-9 levels being a risk factor for fatal outcome or development of neurologic sequelae [35,141,144]. The causative pathogen determines the inflammatory response in patients with bacterial meningitis.…”
Section: Metalloproteinases In the Pathogenesis Of Bacterial Meningitismentioning
confidence: 99%
“…In both places, higher CRP correlated with a lower cerebrospinal fluid glucose concentration (ρ, −0.13; P = 0.04 and ρ, −0.19; P = 0.0003 in LatAm and Luanda, respectively). In Angola, increased CRP also associated with the Glasgow Outcome Score (ρ, −0.11; P = 0.04), initial cerebrospinal fluid matrix metalloproteinase-9 concentration 13 , 14 (ρ, 0.15; P = 0.03), and recovery with neurological sequelae ( P = 0.03).…”
Section: Resultsmentioning
confidence: 97%